Design and Manufacturing of Active Microsystems - Büttgenbach, Stephanus; Burisch, Arne; Hesselbach, Jürgen (Microtechnology and MEMS,, 2011)
This book presents the design and manufacturing of microsystems as well as necessary key technologies developed within the Collaborative Research Center 516. The research efforts of this collaboration are focused on active micro systems which are based on the electromagnetic actuator principle. The travel of the investigated actuator systems is on the order of several millimeters. The total construction size of the actuator is on the range of several centimeters whereas essential structures being several micrometers. The methods and the production technologies that are investigated on the basis of various research models incorporate the fundamental process chains of microsystems.